Sodium Alginate Microneedle Arrays Mediate the Transdermal Delivery of Bovine Serum Albumin - KERİMOĞLU, OYA (PUBLIC LIBRARY SCIENCE, 2013)
Background: The poke and release strategy for the delivery of macromolecules using polymeric microneedle (MN) is of great importance because it eliminates microneedle reuse, the risks of biohazardous sharps and cross contamination, and it requires no special disposal mechanism. The main objective of this study was the determination of the stability and delivery of bovine serum albumin (BSA) that was transported across human skin via sodium alginate (SA) microneedle arrays (MNs) and SA needle free patches using two different analytical methods. Methodology and Findings: The capability of two analytical methods, the bicinchoninic acid (BCA) assay and sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE), to precisely detect and quantify BSA within different types of polymeric MNs was assessed. The ex vivo protein release of BSA across dermatomed human abdominal skin from 10 w/w SA MNs was compared to that from needle-free patches using Franz diffusion cells. The developed applicator was mechanically characterized using a Texture Analyzer. The patch mold and its components were fabricated using a rapid prototyping machine. Conclusions/Significance: The BCA method was able to precisely detect BSA that had been loaded into SA MNs. However, the use of SDS-PAGE as the analytical method resulted in significantly different amounts of BSA recovered from differently conditioned polymeric MNs. The permeation of BSA across dermatomed human abdominal skin by SA MNs, which were composed of 100 pyramidal needles, increased by approximately 15.4 fold compared to the permeation obtained with SA needle-free patches. The ease of use of the applicator during the release studies was also demonstrated, as was its mechanical characterization.
Keywords: SKIN-BARRIER FUNCTION; DRUG; PENETRATION; PATCHES